Significance of Al2O3 addition in the aluminum 6063 metal foam formation through friction stir processing route – A comprehensive study. (December 2021) - Nisa, Sharaf U; Pandey, Sunil; Pandey, PM
Closed-cell porous aluminum is expected to be a prominent material in near future because of its light weight, high specific modulus of elasticity, high energy absorption efficiency and high sound-insulating capacity in the automotive and aerospace industries. Recently, a new method of foaming has been developed in which a precursor is formed using friction stir processing. In the friction stir processing route, a precursor is fabricated by embedding a mixture of blowing agent powder and stabilization agent powder into aluminum alloy plates by the significant stirring action of friction stir processing. By applying the friction stir processing route precursor method, the cost-effective Al-foam formation along with high productivity can be accomplished. In this study, titanium hydride powder has been used as the blowing agent as it is reported to be most compatible with aluminum matrix. The effect of percentage of stabilization agent, i.e. alumina powder on porosity of aluminum foams formed using friction stir processing route is analyzed. The porous aluminum formed with three different percentages of alumina is observed and their porosity is calculated. Also, the compressive performance of the obtained samples is observed in order to examine the alumina powder addition on mechanical properties of the obtained metal foam. This study aims at analyzing the significance of addition of the alumina into the blowing agent while developing the metal foam through friction stir processing route.